Toward Productive, Inclusive, and Sustainable Farms and Agribusiness Firms : An Evaluation of the World Bank Group’s Support for the Development of Agrifood Economies (2010–20) - World Bank (Washington, DC, 2022)
The purpose of the evaluation is to assess how relevant and effective the World Bank Group has been in its support for agrifood system development (AFSD) —that is, in developing more productive, inclusive, and sustainable farms and agribusiness firms. The evaluation finds that the Bank Group’s interventions (FY 2010–20) were broadly relevant, although gaps remain in scaling up and better targeting support to countries that need it the most. Bank Group interventions were also effective overall in improving productivity, inclusion, and sustainability, but less so in LICs, particularly in West and Central Africa. World Bank interventions that focused on supporting production were less successful than interventions that combined production and market approaches. World Bank support for improving productivity was insufficiently diversified toward higher-value products that offer multiple benefits. IFC agribusiness investments faced challenges meeting environmental and social (E&S) standards, especially in LICs. IEG offers three recommendations to enhance Bank Group support for AFSD. (i) To enhance its effectiveness in developing agrifood systems, the World Bank Group’s efforts to support production technologies should be complemented by efforts to improve market access, especially in LICs and in countries at the traditional stage of agrifood system development. These can be pursued through synergies in Bank Group interventions or with partners; (ii) To achieve more sustainable agrifood systems, where conditions permit, the World Bank Group should support production diversification to meet the growing demand for undersupplied high-value-added, nutritious products while ensuring that smallholder farmers and SMEs benefit from the diversification; and (iii) To enhance the contribution of IFC support for AFSD, IFC should pilot and adopt more effective ways to support clients to better meet E&S Performance Standards, especially in LICs.